Colorectal Cancer Prevention in Inflammatory Bowel Disease: A Systematic Analysis of the Overall Quality of Guideline Recommendations. Issue 5 (10th July 2021) - Weissman, Simcha; Systrom, Hannah K; Aziz, Muhammad; El-Dallal, Mohammed; Lee-Smith, Wade; Sciarra, Michael; Feuerstein, Joseph D
Abstract: Background: Owing to the increased risk of colorectal cancer (CRC) in patients with inflammatory bowel disease (IBD), numerous societies developed preventative guidelines. We aimed to assess the overall quality of CRC prevention guidelines in IBD. Methods: A systematic search was performed in multiple databases to identify all guidelines pertaining to CRC prevention in IBD in September 2020. All guidelines were reviewed for conflicts of interest (COIs)/funding, recommendation quality/strength, external guideline review, use of patient representation, and plans for update—as per Institute of Medicine standards. In addition, recommendations were compared amongst societies. Results: One hundred forty-nine recommendations from 14 different guidelines/societies were included. Not all guidelines provided recommendations on key elements surrounding (1) screening initiation and surveillance, (2) screening modality, (3) pharmacological chemoprevention, (4) dysplasia management and follow-up, and (5) molecular marker use. Only 71% of guidelines disclosed COIs, 43% reported industry funding, 14% were externally reviewed, 7% included patient representation, and 36% had plans for update. Of the total recommendations, 7.4%, 23.5%, and 69.1% were based on high, - moderate-, and low-quality evidence, respectively. Additionally, 20.1% of recommendations were strong, 14.1%, were weak/conditional, and 65.8% did not provide a strength. The proportion of high-quality evidence ( P = 0.34) and strong recommendations ( P = 0.57) did not significantly differ across societies. Conclusions: Many guidelines do not provide recommendations on key aspects of CRC prevention in IBD. Over 90% of recommendations are based on low- to moderate-quality evidence; therefore, further studies on CRC prevention in IBD are needed to improve the overall quality of evidence.